Investor Protection and Firm Liquidity - Brockman, Paul; Chung, Dennis Y. (Journal of Finance, 2003)
ABSTRACT The purpose of this study is to investigate the relation between investor protection and firm liquidity. We posit that less protective environments lead to wider bid‐ask spreads and thinner depths because they fail to minimize information asymmetries. The Hong Kong equity market provides a unique opportunity to compare liquidity costs across distinct investor protection environments, but still within a common trading mechanism and currency. Our empirical findings verify that firm liquidity is significantly affected by investor protection. Regression and matched‐sample results show that Hong Kong‐based equities exhibit narrower spreads and thicker depths than their China‐based counterparts.